EVALUASI PROGRAM PELATIHAN TENAGA KERJA BERBASIS KOPETENSI OLEH DINAS TENAGA KERJA KOTA BEKASI TAHUN 2021 - Mochamad Ricky Fajar Dharmawan; Maulana Rifai; Dewi Noor Azijah (Universitas Tribhuwana Tunggadewi, 2022)
The purpose of this study is to describe how to evaluate the Competency-Based Workforce Training Program by the Bekasi City Manpower Office in 2021. The method of this research is descriptive. Data collection techniques using observation, interviews and documentation. The types of data used in this study are primary data and secondary data obtained from interviews with informants in this study. In this study, the author uses the theory of program evaluation according to Daniel Stufflebeam as a reference in analyzing which consists of the dimensions of context, input, process and output. The results of this study indicate that the evaluation of the Competency-Based Workforce Training Program by the Bekasi City Manpower Office is considered feasible to be continued but there are some improvements. From the context and process evaluation dimensions, the overall evaluation was good, but in the input and output evaluation dimensions problems were found such as the lack of teaching or instructor resources and also no monitoring and data collection from the Bekasi City Manpower Office after the training.